The design of a Biochamber for Micropropagation of Banana tissue culture plants and controlling the Biochamber process using Programmable Logic Controller (PLC) - Muhamad Hatta, Hussain; Ismail, Daut; Norlida, Buniyamin; Zainuddin, Mohamad; Norzulaani, Khalid (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my